Halogen-substituted ureas for anion binding: solid state and solution studies - Casula, Arianna; Fornasier, Marco; Montis, Riccardo; Bettoschi, Alexandre; Argent, Stephen P.; Blake, Alexander J.; Lippolis, Vito; Marongiu, Laura; Picci, Giacomo; Tidey, Jeremiah P.; Caltagirone, Claudia (Taylor & Francis, 2017)
Herein, we report the synthesis and the anion binding properties of a family of N,N′-diphenylureas L1-L15, bearing on the aromatic ring(s) halogens (chlorine and iodine) and/or nitro or trifluoromethyl electron-withdrawing groups. The analysis of the crystal structures obtained from single crystal X-ray diffraction experiments shows that self-assembled chains or tapes connected via N–H···O hydrogen bonds are the most commonly adopted arrangements for this type of molecules in the crystal lattice. In the presence of anion guests or solvent molecules with competing hydrogen bond donors and acceptors, other supramolecular arrangements can be observed. Solution studies conducted in DMSOd 6/0.5% H2O by means of 1H-NMR titrations show the formation of 1:1 adducts with all receptors. The different observed affinities of the receptors for the anion guests were rationalised in terms of steric hindrance of the substituents on the phenyl rings and their electron-withdrawing properties.